PENGARUH VIRTUAL REALITY TERHADAP PENGETAHUAN MAHASISWA TENTANG RESPON TANGGAP DARURAT BENCANA DI DALAM GEDUNG - imaru diani (IKesT Muhammadiyah Palembang, 2024)
Introduction: Disasters are events or series of events that threaten and disrupt people's lives and livelihoods caused by both natural and/or non-natural factors and human factors. Fire disasters are one of the disasters that often occur in Indonesia, especially in big cities like Palembang. Fire prevention can actually be done by increasing public awareness of the dangers of fire. Communities must be able to anticipate from an early age the potential threat of fire in their respective environments, by preparing themselves to face the threat of fire. The use of virtual reality is one way of providing education about emergency response to fire disasters because it is interesting and like stimulation that feels real. Objective: to determine the effect of virtual reality on students' knowledge about emergency response to disasters in buildings. Method: Pre-experimental research using one group pretest posttest design. The sample was selected using probability sampling using the consecutive sampling method, a total of 38 students at the IKesT Muhammadiyah Palembang dormitory. The research instrument used a video about emergency response to fire disasters in buildings and a virtual reality box, as well as a knowledge questionnaire. Results: Based on data analysis using the Wilcoxon test, it was found that the p value was <0.05 with a median value before 45 and after 70. Conclusion: There is an influence of virtual reality on students' knowledge about emergency response to disasters in buildings